Investigation of Mental Health Literacy and Status of Residents During the Re-Outbreak of COVID-19 in China - Li, Shiming; Guo, Bingbing; Lu, Xiao; Yang, Queping; Zhu, Haohao; Ji, Yingying; Jiang, Ying (Frontiers in Public Health, 2022)
Introduction The current field of research on the impact of COVID-19 on mental health was mostly limited to the evaluation of the first round of the epidemic, few reports focused on the impact of the re-emergence of COVID-19. This study aimed to investigate the mental health literacy and status of residents during the re-outbreak of COVID-19 in China. Methods The basic information sheet, health literacy survey scale, physical health questionnaire-9 (PHQ-9), generalized anxiety disorder-7 (GAD-7), insomnia severity index (ISI), and Alzheimer dementia 8 (AD8) were applied to evaluate the mental health literacy, mental health status and elderly cognitive function, and χ2 test was applied for analysis of the difference between different groups. Results A total of 2,306 participants were involved in this study, of which 734 people completed the mental health literacy survey. The qualified rate of mental health literacy was 6.4%. The difference is statistically significant. A total of 1,015 people completed the survey of mental health status, the prevalence of depressive symptoms was 8.87%, the monthly income of different families (χ2 = 13.96, P = 0.01), the self-assessed health status (χ2 = 128.56, P < 0.05), the presence or absence of chronic diseases (χ2 = 4.78, P = 0.03), among all which the difference was statistically significant; the prevalence of anxiety symptoms was 3.84%, different regions (χ2 = 12.26, P < 0.05), occupations (χ2 = 11.65, P < 0.05), household monthly income (χ2 = 12.65, P = 0.01), self-rated health status (χ2 = 151.11, P < 0.05), and chronic diseases (χ2 = 7.77, P = 0.01), among all which the differences were statistically significant. The prevalence of insomnia symptoms was 7.98%, different age (χ2 = 18.45, P < 0.05), region (χ2 = 5.11, P = 0.02), monthly household income (χ2 = 12.68 P = 0.01), and self-assessed health status (χ2 = 91.71, P < 0.05), in which there was a statistically significant difference between those with or without chronic diseases (χ2 = 3 3.25, P < 0.05). A total of 557 elderly people over 65 years old completed the cognitive dysfunction screening, in which the prevalence of cognitive dysfunction was 17.41%, and the difference was statistically significant at the different self-assessed health status (χ2 = 96.24, P < 0.05) and with or without chronic diseases (χ2 = 107.09, P < 0.05). Conclusion The mental health literacy and status of residents have not improved significantly during the second outbreak of the epidemic, indicating that under the normalization of epidemic prevention and control, more attention should be paid to the mental health of residents, and targeted health education and psychological intervention should be carried out to avoid relative adverse events.